2020
DOI: 10.3390/s20154282
|View full text |Cite
|
Sign up to set email alerts
|

Non-Contact Evaluation of Pigs’ Body Temperature Incorporating Environmental Factors

Abstract: Internal body temperature is the gold standard for the fever of pigs, however non-contact infrared imaging technology (IRT) can only measure the skin temperature of regions of interest (ROI). Therefore, using IRT to detect the internal body temperature should be based on a correlation model between the ROI temperature and the internal temperature. When heat exchange between the ROI and the surroundings makes the ROI temperature more correlated with the environment, merely depending on the ROI to predict the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…The results also confirmed that the T sk from ASFV-infected pigs was distinct from T core , which was coincident with previous studies [ 1 , 13 , 14 , 16 , 26 ]. Previous studies have also revealed the relationship between T sk and T core in pigs, indicating that they differ depending on the age and breed of pigs, ambient temperature, and region of body measured [ 13 , 16 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results also confirmed that the T sk from ASFV-infected pigs was distinct from T core , which was coincident with previous studies [ 1 , 13 , 14 , 16 , 26 ]. Previous studies have also revealed the relationship between T sk and T core in pigs, indicating that they differ depending on the age and breed of pigs, ambient temperature, and region of body measured [ 13 , 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…Fever or internal temperature ( T core ) in pigs is commonly assessed by measuring rectal temperature with a mercurial thermometer. However, this method is invasive and requires manual handling of animals, which might increase the risk of spreading infectious pathogens within farms [ 1 , 2 ]. Infrared thermography (IRT) is a technique that creates a visible image from the invisible infrared radiation emitted by an object [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this region, in both the rat and the bovine tail, large straight vessels aid to the thermoregulation [ 20 ], and validating thermal windows requires high sensitivity and specificity to predict physiological states accurately. Although this has been achieved in several species [ 44 ], the reliability of this approach is limited by several conditions, such as the presence or absence of hair (glabrous skin), fur thickness, skin thickness, and fur color, all of which can alter heat gain or loss [ 45 ]. In addition, these characteristics establish differences among species, such as those between dogs and rats.…”
Section: Anatomical Locations Of Thermal Windows In Cattle and River Buffalomentioning
confidence: 99%